Case Report: Vogt-Koyanagi-Harada Syndrome Mimicking Acute Angle-Closure Glaucoma in a Patient Infected With Human Immunodeficiency Virus - Bai, Xue; Hua, Rui (Frontiers in Medicine, 2022)
Vogt-Koyanagi-Harada disease (VKH) is a rare multisystemic inflammatory autoimmune disorder. Glaucoma secondary to VKH frequently occurs during the recurrent phase of anterior uveitis; however, acute angle-closure glaucoma (ACG) secondary to both VKH and human immunodeficiency virus (HIV) infection has rarely been reported. We describe a case of secondary acute ACG involving VKH, characterized by sudden vision loss, moderately elevated intraocular pressure (IOP), shallow anterior chamber, and fully or partially closed angle, in an HIV-infected patient. Both VKH and HIV infection contributed to the occurrence of ACG due to the leakage and forward rotation of the ciliary body, as well as choroidal effusion. The deterioration of IOP and serous macular detachment were observed after initial corticosteroid therapy. Visual acuity and IOP were improved with subretinal fluid absorption after continued corticosteroid therapy. Understanding the response of IOP and serous macular detachment after corticosteroid therapy is important for clinical practice.